PORTRAIT OF EGO DEFENSE MECHANISM IN SONG LYRICS SEKUAT SESAKIT - Purnomo, Nourma Ayu Safithri (International Journal of Humanity Studies (IJHS), 2025)
Music is a literary work that serves as a means of psychological expression for individuals. This can be seen in the lyrics of the song Sekuat Sesakit, which describe the ego defense mechanisms of repression and reaction formation. This situation is interesting to study in depth due to the limited research on the analysis of ego defense mechanisms in song lyrics. This study aims to explore how the lyrics of the song Sekuat Sesakit reflect ego defense mechanisms and their impact on an individual's psychological condition. This study uses the hierarchy of ego defense mechanisms theory described by George Vaillant. The object of study in this research is the lyrics of the song Sekuat Sesakit performed by Idgitaf. This study uses a qualitative method with a thematic analysis technique. The results of this study show that repression and reaction formation fall into the neurotic level of the ego defense mechanism theory. The long-term use of repression and reaction formation can cause psychological disorders that negatively affect an individual's mental health. The information from this study is expected to add to the understanding of the concept of ego defense mechanisms through song lyrics from a psychological perspective.